PENGARUH LOKASI DAN KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN TAMU DI RISS HOTEL MALIOBORO YOGYAKARTA - Luluk Kholisoh; Kemala Fidela Salvia Saputro; Rini Susilawati; Aris Risdiana; Sapta Aji Margiutomo (Kajian Ekonomi dan Bisnis, 2025)
The development of the hotel industry in Yogyakarta, particularly in the Malioboro area, has driven increasingly fierce competition among hotels. Riss Hotel Malioboro, as a star-rated hotel, is required to maintain and enhance guest satisfaction through location and service quality. This study aims to determine the influence of location and service quality on guest satisfaction at Riss Hotel Malioboro Yogyakarta. This study used quantitative methods. Data were obtained through a questionnaire distributed to 127 respondents and then analysed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that both location and service quality have a positive and significant effect on guest satisfaction, both partially and simultaneously. The results indicate that the more strategic the hotel's location and the better the service quality, the higher the level of guest satisfaction at Riss Hotel Malioboro. Keywords: Location, Service Quality, Guest Satisfaction, Riss Hotel Malioboro